2020
DOI: 10.1177/1750458920907885
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and outcomes after implementation of an enhanced recovery surgical protocol in older women undergoing pelvic reconstructive surgery

Abstract: The aim of this study is to evaluate compliance and outcomes with implementation of an enhanced recovery surgical protocol in older women undergoing pelvic reconstructive surgery. This is a retrospective cohort study of women undergoing pelvic reconstructive surgery after implementation of the pathway over a 12-month period. Overall compliance was defined as a categorial variable requiring adherence to all of the selected bundle components in patients <65 years old compared to those ≥65. Intraoperative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…In one such study, data were collected for the full year preceding implementation 123 . Another study specific to urogynecological patients showed increased compliance after implementation from 19% to 77% over the 12-month study period 121 . This is consistent with other studies in gynecological literature 124 .…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…In one such study, data were collected for the full year preceding implementation 123 . Another study specific to urogynecological patients showed increased compliance after implementation from 19% to 77% over the 12-month study period 121 . This is consistent with other studies in gynecological literature 124 .…”
Section: Resultssupporting
confidence: 75%
“…These results may also be generalizable in urogynecology. After implementation, regular perioperative team meetings may be held to review compliance and audit outcomes to improve or modify portions of the ERAS protocol as needed 121 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, 493 articles were screened. Among them, 477 were excluded based on their title and/or abstract, thus, 16 articles were retrieved as full-texts 16–31 …”
Section: Resultsmentioning
confidence: 99%